Determining the Phosphorus Release of GraINzyme Phytase in Nursery Pigs - Larissa L. Becker; Madie R. Wensley; Joel M DeRouchey; Jason C. Woodworth; Mike D. Tokach; Robert D. Goodband; Jordan T. Gebhardt; R. Michael Raab; Philip A. Lessard (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 360 pigs (200 × 400, DNA; initially 21.9 ± 0.42 lb) were used in a 21-d growth trial to determine the available P (aP) release curve for GraINzyme Phytase (Agrivida Inc., Woburn, MA). Pigs were weaned at approximately 21 d of age, randomly allotted to pens based on initial BW and fed common starter diets. From d 18 to 21 post-weaning, all pigs were fed a diet containing 0.11% aP. On d 21 post-weaning, considered d 0 of the study, pens were blocked by BW and randomly allotted to 1 of 8 dietary treatments with 5 pigs per pen and 9 pens per treatment. Dietary treatments were formulated to include increasing aP derived from either an inorganic P source (0.11, 0.19, or 0.27% from monocalcium P) or increasing levels of phytase (150, 250, 500, 1,000, or 1,500 FTU/kg). Diets were corn-soybean meal-based and contained 1.24% standardized ileal digestible (SID) Lys. On d 21 of the trial, 1 pig per pen (weighing closest to the mean pen BW) was humanely euthanized and the right fibula was collected to determine bone ash using the non-defatted processing method. Overall (d 0 to 21), pigs fed increasing aP from inorganic P or phytase had improved (linear,P<0.002) ADG, ADFI, and F/G. Bone ash weight and percentage bone ash increased (linear,P<0.001) with increasing inorganic P or added phytase. Based on these results, the release equations developed for GraINzyme for ADG, G:F, bone ash weight, and percentage bone ash are: aP = (0.255 × FTU) ÷ (1299.969 + FTU); aP = (0.233 × FTU) ÷ (1236.428 + FTU); aP = (45999.949 × FTU) ÷ (462529200 + FTU); and aP = (0.272 × FTU) ÷ (2576.581 + FTU), respectively.
Keywords: bone ash; nursery pigs; phosphorus; phytase